Daniel Solomon: An Appreciation Why Architects in Practice should Teach (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2020)
Bennett identifies in Solomon’s work a paradigm for deep understanding of urban situations which can produce sympathetic, constructive interventions in existing cities, and paradigms for new ones. Solomon is seen as a paradigm of values for professionals teaching in universities.